Clinical and haemodynamic evaluation of chronic thromboembolic pulmonary hypertension patients scheduled for pulmonary thromboendarterectomy: Is schistosomiasis hypertension an important confounding factor? - Terra-Filho, Mario (2010)
INTRODUCTION: Chronic thromboembolic pulmonary hypertension is a disease affecting approximately 4,000 people per year in the United States. The incidence rate in Brazil, however, is unknown. The estimated survival for patients with chronic thromboembolic pulmonary hypertension without treatment is approximately three years. Pulmonary thromboendarterectomy for select patients is a potentially curative procedure when correctly applied. In Brazil, the clinical and hemodynamic profiles of chronic thromboembolic pulmonary hypertension patients have yet to be described. OBJECTIVES: To evaluate the clinical and hemodynamic characteristics of chronic thromboembolic pulmonary hypertension patients scheduled for pulmonary thromboendarterectomy in a referral center for chronic thromboembolic pulmonary hypertension treatment in Brazil. METHODS: From December 2006 to November 2009, patients were evaluated and scheduled for pulmonary thromboendarterectomy. The subjects were classified according to gender, age and functional class and were tested for thrombofilia and brain natriuretic peptide levels. RESULTS: Thirty-five consecutive chronic thromboembolic pulmonary hypertension patients were evaluated. Two patients tested positive for schistosomiasis, and 31 were enrolled in the study (19 female, 12 male). The majority of patients were categorized in functional classes III and IV. Hemodynamic data showed a mean pulmonary vascular resistance (PVR) of 970.8 ± 494.36 dynas·s·cm-5 and a low cardiac output of 3.378 ± 1.13 L/min. Linear regression revealed a direct relation between cardiac output and pulmonary vascular resistance. Paradoxical septal movement was strongly correlated with pulmonary vascular resistance and cardiac output (p=0.001). Brain natriuretic peptide serum levels were elevated in 19 of 27 patients. CONCLUSIONS: In a referral center for pulmonary hypertension in Brazil, chronic thromboembolic pulmonary hypertension patients evaluated for pulmonary thromboendarterectomy had a hemodynamically severe status and had elevated brain natriuretic peptide serum levels. There was a predominance of females in our cohort, and the prevalence of hematological disorders and schistosomiasis was low (less than 10%).